1985
DOI: 10.1155/s0161171285000540
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of convergence in fuzzy topological spaces

Abstract: ABSTRACT. In a fuzzy topology on a set X, the limit of a prefilter (i.e. a filter in the lattice [0,i]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…There are lots of papers [4][5][6]8,9,18,19,26] that focus on fuzzy convergence theory based on fuzzy filters. In [18], Lowen considered prefilters (which are filters in the lattice [0, 1] X ) in the theory of convergence in fuzzy topological spaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are lots of papers [4][5][6]8,9,18,19,26] that focus on fuzzy convergence theory based on fuzzy filters. In [18], Lowen considered prefilters (which are filters in the lattice [0, 1] X ) in the theory of convergence in fuzzy topological spaces.…”
Section: Introductionmentioning
confidence: 99%
“…In [18], Lowen considered prefilters (which are filters in the lattice [0, 1] X ) in the theory of convergence in fuzzy topological spaces. Further Lowen and Lowen [19] gave a necessary and sufficient condition for convergence functions to be induced by fuzzy topologies. Later on, Jäger [8] introduced stratified L-fuzzy convergence spaces and showed that the category of stratified L-topological spaces can be embedded in the category of stratified L-fuzzy convergence spaces as a reflective subcategory.…”
Section: Introductionmentioning
confidence: 99%
“…In 1979 Lowen [20] introduced and studied the theory of convergence for fuzzy filters (prefilters) in fuzzy topological spaces and applied the results to describe fuzzy compactness and fuzzy continuity. This was followed by an extensive study of the convergence theory of fuzzy filters in fuzzy topological spaces by several authors [7], [9]- [12], [21], [22], [26], [27], [31] from different standpoints. However, the concepts of Q-relation and Q-neighborhood of fuzzy points have not been used in these approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In 1980 Pu and Liu [28], by means of the concept of a Q-neighborhood of a fuzzy point in a fuzzy topological space, gave the notion of convergence for fuzzy nets. The relationship between the two types of convergence was studied by Lowen in [21]. This was also followed by an extensive study of the convergence theory in fuzzy topological spaces by several authors [7], [8], [13], [21]- [24], [28]- [30] from different standpoints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation